Emplacing a Cooling-Limited Rhyolite Lava Flow: Similarities with Basaltic Lava Flows - Magnall, Nathan; James, Mike R.; Tuffen, Hugh; Vye-Brown, Charlotte (Frontiers in Earth Science, 2017)
Accurate forecasts of lava flow length rely on estimates of eruption and magma properties and, potentially more challengingly, on an understanding of the relative influence of characteristics such as the apparent viscosity, the yield strength of the flow core, or the strength of the lava's surface crust. For basaltic lavas, the relatively high frequency of eruptions has resulted in numerous opportunities to test emplacement models on such low silica lava flows. However, the flow of high silica lava is much less well understood due to the paucity of contemporary events and, if observations of flow length change are used to constrain straightforward models of lava advance, remaining uncertainties can limit the insight gained. Here, for the first time, we incorporate morphological observations from during and after flow field evolution to improve model constraints and reduce uncertainties. After demonstrating the approach on a basaltic lava flow (Mt. Etna 2001), we apply it to the 2011–2012 Cordón Caulle rhyolite lava flow, where unprecedented observations and syn-emplacement satellite imagery of an advancing silica-rich lava flow have indicated an important influence from the lava flow's crust on flow emplacement. Our results show that an initial phase of viscosity-controlled advance at Cordón Caulle was followed by later crustal control, accompanied by formation of flow surface folds and large-scale crustal fractures. Where the lava was unconstrained by topography, the cooled crust ultimately halted advance of the main flow and led to the formation of breakouts from the flow front and margins, influencing the footprint of the lava, its advance rate, and the duration of flow advance. Highly similar behavior occurred in the 2001 Etna basaltic lava flow. In our comparison of these two cases, we find close similarities between the processes controlling the advance of a crystal-poor rhyolite and a basaltic lava flow, suggesting common controlling mechanisms that transcend the profound rheological and compositional differences of the lavas.